Complications after direct anterior versus Watson-Jones approach in total hip arthroplasty: results from a matched pair analysis on 1408 patients - Antonio Klasan; Thomas Neri; Ludwig Oberkircher; Dominik Malcherczyk; Thomas Jan Heyse; Christopher Bliemel (BMC Musculoskeletal Disorders, 2019)
Abstract Background The direct anterior approach (DAA) has gained popularity in total hip arthroplasty (THA) over the past decade. A large number of studies have compared the DAA to other approaches with inclusion of a learning curve phase. The aim of this study was to compare the complication rate and bleeding between the DAA and the anterolateral approach after the learning curve phase. Methods For this retrospective, single-institutional study, propensity score matching was performed, from an initial cohort of 1408 patients receiving an elective THA. Two matching groups were created, comprising of 396 patients each. After matching, both groups were similar in age, gender, body mass index, anesthesiologist’s score and surgeon’s experience. Results Average age in the matched groups was 68.7 ± 10.3 years. The total blood loss was similar in both groups, 450 vs 469 mL (p = 0.400), whereas the transfusion rate (14.1 vs 5.8%, p < 0.001) and the overall complication rate (17.6 vs 12.1%, p = 0.018) were lower in the DAA group. The overall fracture rate was comparable, 1.5 vs 1% (p = 0.376), as well as the early infection rate, 0.3 vs 1% (p = 0.162). The dislocation rate was significantly increased in the DAA group, 2.2 vs 0.5% (p = 0.032). Conclusions The direct anterior approach has comparable short-term surgical complications with reduced transfusion and general complication rates. Level of evidence Level III retrospective study.